Pengembangan Media Pembelajaran Interaktif “Jejak Pancasila” Berbasis Articulate Storyline untuk Meningkatkan Kemampuan Berpikir Kritis Siswa Sekolah Dasar - Liza Wahyu Utami; Afandi, Muhamad (Kartika: Jurnal Studi Keislaman, 2026)
This study focuses on the challenge of low student engagement in learning, largely attributed to conventional lecture-based methods that lead to learning fatigue, particularly in Pancasila formulation material. This condition underscores the need for innovative learning media capable of creating engaging and meaningful learning experiences. This study aims to examine the feasibility, practicality, and effectiveness of the Jejak Pancasila interactive learning media. The study employed a Research and Development (R&D) approach based on the ADDIE model, involving students of SDN 1 Tribuana in the 2025/2026 academic year. Data analysis included media validation, teacher and student response questionnaires, and critical thinking test instruments. Validator assessments yielded the following percentages: media expert 88%, content expert 95%, and language expert 92%, with an overall average of 91.7%, categorized as highly feasible. Empirically, the mean pre-test score of 60.5 increased to 67.2 on the post-test. The paired sample t-test produced a significance value of 0.002 < 0.05, indicating significant differences in learning outcomes before and after treatment. The N-Gain score of 0.158 indicates improvement remains in the less effective category. The Jejak Pancasila interactive media can be further developed as a reference for other subject matter.